2017
DOI: 10.1177/000313481708300731
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in the Care of Differentiated Thyroid Cancer in the United States: Exploring the National Cancer Database

Abstract: Differentiated thyroid cancer (DTC) treatment is multifaceted, and may be influenced by socio-economic factors. The goal of this study is to examine disparities in DTC treatment. DTC patients from 1998 to 2012 were identified using the National Cancer Database. DTC was identified in 262,041 patients. The mean age was 48.2. The majority of patients (52%) received care at Comprehensive Community Cancer Programs (CCCPs). Total thyroidectomy was less common at Community Cancer Programs (CCPs) [odds ratio (OR): 0.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Given that previous studies highlighted the racial and ethnic disparities in presentation, treatment, and prognosis of patients with DTC, [7][8][9][10][12][13][14] we examined whether adoption of the AJCC8 staging system affected the prognosis of self-reported racial and ethnic groups equally. Our study is the first to demonstrate that downstaging did affect self-reported race and ethnic groups differently.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that previous studies highlighted the racial and ethnic disparities in presentation, treatment, and prognosis of patients with DTC, [7][8][9][10][12][13][14] we examined whether adoption of the AJCC8 staging system affected the prognosis of self-reported racial and ethnic groups equally. Our study is the first to demonstrate that downstaging did affect self-reported race and ethnic groups differently.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies reported that blacks had a higher incidence of follicular variant of PTC (FVPTC), a higher potential of developing distant metastasis from FVPTC, were less likely to receive appropriate thyroid surgery compared with whites, and were also less likely to have received radioactive iodine. [6][7][8][9][10][11] Moreover, in a study of adolescents and young adults with DTC in California, thyroid cancer-specific mortality was decreased in blacks and Hispanics. 10 Taking into account the significant disparities that exist among self-reported racial and ethnic groups in DTC, the hypothesis of our study was that the changes in staging (i.e., down-staging) introduced by the AJCC8 impacted the prognosis of racial and ethnic groups differently.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only the annual household income had a significant effect on VAS change 1 year postoperatively compared with pre‐operative status. In the US, a delayed diagnosis and therapy of thyroid cancer have been shown in black and uninsured patients as well as in families with low income . Although the German cannot be compared with the American health system, it seems that the household income affects health‐related QoL in thyroid disease transnationally.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have observed differences in patterns of care for a variety of cancer sites (e.g. breast, thyroid) at different types of cancer centers, which have evolved over time [ 10 , 11 ]. In this study we obtained available data from the NCDB on variables included in the management of SCCA in the United States to compare patient demographics and care delivery between ACPs and CCPs.…”
Section: Introductionmentioning
confidence: 99%